Peranan Jabatan Agama Islam Selangor (JAIS) dalam menangani isu ekstremisme di Selangor [Roles of Selangor Islamic religious department to handle extremist issues in Selangor] - Mohd Hasrul, Shuhari; Najihah, Abd Wahid; Nur Solehah, Mohd Yazid (Penerbit Universiti Sultan Zainal Abidin, 2020)
Islam is a religion that brings peace and harmony to all mankind, whether from a theoritical or practical point of view; wasattiyah in his practice. However, Islam has often been related to acts of violence especially in Southeast Asia such as the Bali bombings by the jemaah islam in 2002, the Paris bombing in 2015, the Abu Sayyaf movement in the Philippines and the nightclub bombings in Puchong in 2017. by extremist Islamic State groups (IS). Focus in Malaysia, this study explains the roles of the Selangor Islamic Religious Department (JAIS) in addressing issues of religious extremism and challenges in Selangor such as IS. This qualitative study uses interview method and documentation method. This study is expected to contribute to the development of an academic source and references to extremism-themed research especially on the roles and strategy of the Selangor Islamic Religious Department in addressing the critical issues of the current Ummah.